2009
DOI: 10.1097/mco.0b013e328329e4ef
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the management of intestinal failure-associated liver disease

Abstract: A greater understanding of the mechanisms of IFALD has led to promising interventions to prevent and treat the condition. Other possible therapeutic targets require more formal evaluation, and further work is required to develop noninvasive tools for the assessment and prognosis of IFALD that will guide treatment and help in the selection of patients and timing of transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Triglycerides could, therefore, be used not only as a prognostic factor, but also as an observed indicator in a subsequent nutrition therapy study in patients with ACLF. Other studies have revealed that liver nutrition therapy may improve the prognosis [24][28]. Moreover, the association of triglycerides with mortality in patients with ACLF will be of interest in subsequent studies.…”
Section: Discussionmentioning
confidence: 97%
“…Triglycerides could, therefore, be used not only as a prognostic factor, but also as an observed indicator in a subsequent nutrition therapy study in patients with ACLF. Other studies have revealed that liver nutrition therapy may improve the prognosis [24][28]. Moreover, the association of triglycerides with mortality in patients with ACLF will be of interest in subsequent studies.…”
Section: Discussionmentioning
confidence: 97%
“…The somatostatin was also reported to be detrimental by reducing splanchnic blood flow and nutrient absorption [19]. EN, as opposed to PN, has been shown to improve intestinal barrier function, reduce the risk of bacterial translocation, and attenuate liver dysfunction [20]. EN is effective in downregulating inflammation response, reducing oxidative stress, and improving outcomes [21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies are ongoing on the role of omega-3 lipids (Omegaven) in treating and preventing PNALD and are very encouraging Rollins et al 2010;Premkumar et al 2013). Weaning patients off PN as early as possible by optimizing EN remains the only way to prevent PNALD (Wiles and Woodward 2009). …”
Section: Parenteral Nutrition Associated Liver Disease (Pnald)mentioning
confidence: 97%